1997
DOI: 10.1111/j.1502-3931.1997.tb00470.x
|View full text |Cite
|
Sign up to set email alerts
|

The Ocruranus–Eohalobia group of small shelly fossils from the Lower Cambrian of Yunnan

Abstract: Lower Cambrian phosphorite samples from Maotianshan, Yunnan Province, South China, yielded a variety of small shelly fossils. Sclerites of the second pre‐trilobite faunal assemblage of Meishucun, the Paragbborilus‐Siphogonuchites–Lapworthella association of Nemakit–Daldynian to Tommotían age, were dominant. They comprise previously unknown spine‐bearing specimens of Ocruranus finial Liu, 1979, and new morphotypes of Eohalobia diandongensis Jiang, 1982. Well‐preserved sclerites reveal a laminated, composite fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 7 publications
2
20
1
Order By: Relevance
“…A relationship of some sort between Eohalobia and Ocruranus is now generally accepted (e.g. Siegmund 1997; Conway Morris and Caron 2007), but the taxonomic affinity of this group remains controversial.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A relationship of some sort between Eohalobia and Ocruranus is now generally accepted (e.g. Siegmund 1997; Conway Morris and Caron 2007), but the taxonomic affinity of this group remains controversial.…”
mentioning
confidence: 99%
“…Bengtson (1992, p. 411) mentioned the ‘distinct possibility’ that these fossils are part of a coeloscleritophoran scleritome, noting that even though they appear to have a smooth shell surface, they have an apical re‐entrant (‘apical area’ in chiton terminology) like in those of co‐occurring scaly shells similar to Maikhanella . The hypothesis of coeloscleritophoran affinity was argued more forcibly by Siegmund (1997), who suggested that Ocruranus – Eohalobia , like Maikhanella , had a scaly or granular shell, not a smooth shell as Bengtson (1992) had proposed. A coeloscleritophoran affinity was also suggested by Conway Morris and Caron (2007), who commented that the shell plates of Ocruranus and Eohalobia are similar to the shells of halkieriids and halwaxiids.…”
mentioning
confidence: 99%
“…In addition, calcite now appears to have been common in the Ocruranus–Eohalobia group (Siegmund ) and molluscs (Vendrasco & Checa ) in the Terreneuvian, with many mollusc species exhibiting foliated calcite (Vendrasco et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…); (2) the shells are composed of a variety of minerals, including phosphate, calcium carbonate and siliceous mineralization, and that most of the steinkerns preserved as phosphatic fossils have experienced phosphatization (Zhu et al . ); (3) studies of Ocruranus–Eohalobia (Siegmund ) indicated that the primary shell mineral of the Ocruranus–Eohalobia group was probably carbonate. Vendrasco et al .…”
mentioning
confidence: 99%
“…This genus was originally described from the early Cambrian (Meishucunian Stage) of South China as a brachiopod (Liu 1979), but later authors referred the genus to tommotiids, polyplacophorans and coeloscleritophorans (Jiang 1980;Liu 1987;Yu 1987;Qian & Bengtson 1989;Bengtson 1992;Siegmund 1997). Peel and Skovsted (2005) described fossil shells from the lower Cambrian of North-East Greenland very similar in morphology to at least one of the Chinese species referred to Ocruranus (originally described as Stephaconus trulliformis Jiang, 1980) and suggested that these shells represented univalved helcionelloid molluscs.…”
Section: Introductionmentioning
confidence: 99%